2016
DOI: 10.17533/udea.rccp.v29n4a02
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative status and fertility of ewes supplemented coffee pulp during estrous synchronization and early pregnancy

Abstract: Oxidative status and fertility of ewes supplemented coffee pulp during estrous synchronization and early pregnancy ¤ Estado oxidativo y fertilidad en ovejas suplementadas con pulpa de café durante la sincronización estral y gestación tempranaEstado oxidativo e fertilidade nas ovelhas suplementadas com a polpa de café durante sincronização do estro e gestação inicial SummaryBackground: it is known that coffee pulp can modify the oxidative status and fertility in dairy cows. Objective: to evaluate the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Additionally, the digestibility decreases linearly with the inclusion of coffee husks (Souza et al 2006). In sheep, adding 112.5 g of coffee pulp to the diet daily during estrus synchronization and early gestation reduces the pregnancy rate, probably due to the caffeine concentration present in the by-product (Salinas-Rios et al 2016), which is a stimulant of the central nervous system (González and Ramirez-Mares, 2014). In addition to caffeine, coffee pulp contains natural antioxidants (Salinas et al 2014), which have been observed to improve the immune response (Morán et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the digestibility decreases linearly with the inclusion of coffee husks (Souza et al 2006). In sheep, adding 112.5 g of coffee pulp to the diet daily during estrus synchronization and early gestation reduces the pregnancy rate, probably due to the caffeine concentration present in the by-product (Salinas-Rios et al 2016), which is a stimulant of the central nervous system (González and Ramirez-Mares, 2014). In addition to caffeine, coffee pulp contains natural antioxidants (Salinas et al 2014), which have been observed to improve the immune response (Morán et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of pulp for a short period prior to breeding did not affect the reproductive variables. In a previous study (Salinas-Rios et al, 2016), we found that supplementing with 450 g of concentrate with 25% of coffee pulp (corresponding to a coffee pulp consumption of 112.5 g per day) for 25 days before and 25 days after CIDR withdrawal resulted in decreased gestation percentage, which was attributed to the caffeine present in coffee pulp. If ewes consumed 1.5 kg feed, then pulp consumption was 75 g for the treatment with 5% inclusion, and 150 g for the treatment with 10%.…”
Section: Reproductive Performancementioning
confidence: 84%
“…If ewes consumed 1.5 kg feed, then pulp consumption was 75 g for the treatment with 5% inclusion, and 150 g for the treatment with 10%. On average, 5% inclusion corresponds to a lower level, and 10% at a higher level than previously offered (Salinas-Rios et al, 2016); therefore, we assume that up to 10% pulp supplementation for a short period is feasible, although the maximum inclusion should be evaluated.…”
Section: Reproductive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that oxidation stress increases at the time of parturition (Casamassima et al, 2012). Salinas et al (2016) reported that at the beginning of gestation, the antioxidant capacity in blood plasma of sheep decreases. A possible explanation is that the antioxidant concentration decreases, since it has been reported that the concentration of vitamin C, which is an antioxidant, decreases at the beginning of gestation (Salinas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%